Performance Evaluation of Produced Water Quality from a Nearshore Oil Treatment Facility - DBM Nwokoma; KK Dagde (Journal of Applied Sciences and Environmental Management)
Produced water, which is a mixture of organic and inorganic compounds, is a major waste stream generated in oil and gas industries. Its negative impacts on the receiving water bodies have become a worrisome environmental issue. The effluent quality of a crude Oil processing and exporting installation located in the coastal area of the Niger Delta was studied for six months to ascertain the efficiency of the company’s produced water treatment processes. Physicochemical parameters were monitored at the inlet and outlet of the produced water treatment plant. Parameters examined were Temperature, pH, Oil and Grease, Total Dissolved Solids TDS, Total Suspended Solids TSS, Biological Oxygen Demand BOD5. The average temperature of the produced water was reduced from 42.0oC to 25.9oC. The average pH of the samples, which was mostly alkaline prior to treatment, improved from 6.3 to 6.7. The Oil and Grease was reduced from 645.3mg/l to 8.2mg/l. The average concentration of the TDS was reduced from 3836.2mg/l to 965.8mg/l, while the average TSS was reduced from 72.5mg/l to 31.0mg/l. The average Biological Oxygen Demand was reduced from 986.0mg/l to 92.0mg/l. The produced water treatment facility had capability of bringing the final effluent to dischargeable limit. @JASEM